2015
DOI: 10.1002/ange.201503575
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralization of a Cadmium Chloride Nanocrystal by a Designed Symmetrical Protein

Abstract: We have engineered am etal-binding site into the novel artificial b-propeller protein Pizza. This new Pizza variant carries two nearly identical domains per polypeptide chain, and forms at rimer with three-fold symmetry.T he designed single metal ion binding site lies on the symmetry axis, bonding the trimer together.T wo copies of the trimer associate in the presence of cadmium chloride in solution, and very highresolution X-raycrystallographic analysis reveals ananocrystal of cadmium chloride,s andwiched bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…Several organic ligands have been developed to stabilize small nanoclusters and crystal structures have been obtained, but the formation mechanism remains unknown464950. Similarly, protein scaffolds are also used for preparing small nanoclusters, but their exact positions, structures and formation mechanisms remain unclear10111213. In this regard, the present work provides a detailed map for studying the mechanism of formation of inorganic materials in the confined protein environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several organic ligands have been developed to stabilize small nanoclusters and crystal structures have been obtained, but the formation mechanism remains unknown464950. Similarly, protein scaffolds are also used for preparing small nanoclusters, but their exact positions, structures and formation mechanisms remain unclear10111213. In this regard, the present work provides a detailed map for studying the mechanism of formation of inorganic materials in the confined protein environment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cobalt oxide nanoparticles are fabricated in the ferritin cage and an Fe 3 O 4 nanocluster is formed in Dps-like ferritin1018. The metal oxide/chloride cluster in the symmetric protein scaffold does not grow to generate a larger mineral and thus it can serve as an electron transfer centre1213. Several organic ligands have been developed to stabilize small nanoclusters and crystal structures have been obtained, but the formation mechanism remains unknown464950.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1l) (Brunette et al 2015;Doyle et al 2015;Park et al 2015;Parmeggiani and Huang 2017). Mou et al also reported a computationally designed symmetric protein homodimer (Mou et al 2015a), and Voet et al reported computationally designed symmetrical β-propeller proteins (Voet et al 2014) and biomineralization of a cadmium chloride nanocrystal using a designed symmetrical protein (Voet et al 2015). Furthermore, Woolfson and colleagues described computational design of water-soluble α-helical barrels (Thomson et al 2014) and recently installed hydrolytic activity into a de novo α-helical barrel comprising seven helices with cysteine-histidine-glutamate catalytic triads (Burton et al 2016).…”
Section: Rational and Computational Approaches For Hierarchical Desigmentioning
confidence: 99%
“…Creating a protein to perform a predefined or novel biological function(s) is often considered as protein design. In general, protein design is formulated as composing an amino acid sequence which should ideally fold into a stable structure, meant to perform some biological function(s) 9‐13 . The goals of protein design include either desired optimization of certain characteristics such as stability, solubility, and binding affinity or designing entirely novel sequences resulting into novel structures or attaining remedial or industrial utilities 14‐17 .…”
Section: Introductionmentioning
confidence: 99%